Ecoepidemiologia da leishmaniose tegumentar americana no município de Barra do Garças, Mato Grosso, Brasil - Sinara Cristina de Moraes (2015)
The American Cutaneous Leishmaniasis undergo changes in the epidemiological profile, which is associated with environmental transformations and this aspects probably are affecting the epidemiological pattern in the Middle Araguaia region, specifically in the municipality of Barra do Garças MT, the third main area for diseases transmission in number of affected people in the state of Mato Grosso. Thus the present study aimed to characterize some of the ecoepidemiological aspects involved in the transmission pattern of this diseases, mainly by sand flies species identification, population density, urbanization and domiciliation as well as the influence of climate variables such as temperature, relative humidity and rainfall over the distribution pattern and vector density Lutzomyia (Lutzomyia) longipalpis and L. (Nyssomyia) whitmani; to diagnose the natural infection with Leishmania sp., the feeding preferences of Lutzomyia (L.) longipalpis and L. (N.) whitmani, the role of livestock in maintaining the population of sandflies and the epidemiology of human cases. Collections were carried out monthly in urban areas in the intra- and peridomestic and wild area using CDC light traps in 23 points from begins August 2013 to December 2014 afterwards. Some sandflies females specimens were subjected to DNA extraction and PCR reaction to investigate the Leishmania spp. natural infection and food preference. Collected were 10, 843 sandflies, belonging thirty-four species of Lutzomyia, and one of Brumptomyia genus. The most abundant species were L. (L). Longipalpis (38.47%), followed by L (N). whitmani (24.21%) and L. (L.) cruzi (12.65%), totalizing together 75.3% and the remaining 32 species accounted for 24.67%. Considering the places of collection, the peridomicile showed 41.64% L (L.) longipalpis and 17.19% of L. (N.) whitmani, the intradomicile contributed with 60.36%, were L. (N.) whitmani and 25.69% L (L.) longipalpis. Analysing the species abundance of L. (N.) whitmani and L. (L.) cruzi during the dry and rainy seasons, it was verified significant differences between this species. From L. (L.) longipalpis samples it was found three (1.2%) tested positive for L. (I.) chagasi and L. (V.) naiffi Infections, It was also observed that the feeding preference showed predominant bands for chicken blood (28.23%), followed by rodent (25%). The presence of chickens influenced the abundance of sandflies. From January 2007 to December 2014 were reported and confirmed 546 cases of LTA, now being considered urban transmission, with a tax of 60.9% for men and 39.1% for women. The occurrence of cases predominated in people aged between 41 and 50 (18.5%), aged 21 to 30 years (17.4%) and between 11 to 20 years (17.2%). The data confirm the urbanization of L. (L.) longipalpis and L. (N.) whitmani and highlighting a possible domiciliation of L. (N.) whitmani. The results also indicate that peridomiciliary area with the presence of chicken is the main site of importance for maintaining the sandflies life cycle and a point to a new occurrence profile of the American Cutaneous Leishmaniasis.